1998
DOI: 10.1007/s002030050552
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and tactic response of the phototrophic consortium " Chlorochromatium aggregatum "

Abstract: The phototrophic consortium "Chlorochromatium aggregatum" was enriched from sediment samples of a eutrophic freshwater lake and was maintained at high numbers in anoxic sulfide-reduced medium. Growth of intact consortia was observed only in the light and in the presence of 2-oxoglutarate as an organic carbon source. Consortia of "C. aggregatum" reached maximum growth rates at light intensities >/= 5 &mgr;mol quanta m-2 s-1. Of ten compounds tested, sulfide, thiosulfate, 2-oxoglutarate, and citrate served as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 14 publications
3
74
0
Order By: Relevance
“…These two responses may bias the swimming pattern of R. sphaeroides RK1 toward its most favorable light climate for photosynthesis, while simultaneously allowing it to avoid radiation damage. This pattern of opposite responses, as a function of either the color or the intensity of the actinic illumination, is often seen in phototrophic prokaryotes and algae (4,8,13,15,21).…”
Section: Discussionmentioning
confidence: 91%
“…These two responses may bias the swimming pattern of R. sphaeroides RK1 toward its most favorable light climate for photosynthesis, while simultaneously allowing it to avoid radiation damage. This pattern of opposite responses, as a function of either the color or the intensity of the actinic illumination, is often seen in phototrophic prokaryotes and algae (4,8,13,15,21).…”
Section: Discussionmentioning
confidence: 91%
“…This and similar consortia involving photosynthetic sulfur bacteria are highly successful, and occur worldwide in ponds that contain a lower H 2 S-rich layer [42]. It has been questioned whether H 2 S is transferred directly from species to species [43], but since the outer bacteria are obligate H 2 S consumers, sulfide oxidation is certainly involved.…”
Section: Methanogenic Syntrophy (Fig 5)mentioning
confidence: 99%
“…Based on the discovery of interspecies electron transfer through a sulfur cycle between phototrophs and chemotrophs in the undefined coculture 'Chloropseudomonas ethylica' (Biebl & Pfennig 1978), it was assumed that also in these consortia electron transfer proceeds through sulfur compounds, but this assumption could never be verified because no cultures of these consortia were available. Fröstl & Overmann (1998) have recently tackled this diffi-cult issue again and obtained highly enriched cultures of 'Chlorochromatium aggregatum' through enrichment based on skillful chemotaxis studies. It turned out that the consortium can be enriched with 2-oxoglutarate to which it is chemotactically attracted (Fröstl & Overmann 1998).…”
Section: Phototrophic Consortiamentioning
confidence: 99%
“…Fröstl & Overmann (1998) have recently tackled this diffi-cult issue again and obtained highly enriched cultures of 'Chlorochromatium aggregatum' through enrichment based on skillful chemotaxis studies. It turned out that the consortium can be enriched with 2-oxoglutarate to which it is chemotactically attracted (Fröstl & Overmann 1998). 16S rRNA probing revealed that the chemotrophic central bacterium in these consortia belongs to the β-proteobacteria and is highly unlikely to reduce sulfur compounds (Fröstl & Overmann 2000).…”
Section: Phototrophic Consortiamentioning
confidence: 99%